2020
DOI: 10.1371/journal.pone.0229299
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of SUVmax on 18F-fluorodeoxyglucose PET/CT scan in patients with malignant pleural mesothelioma

Abstract: IntroductionThe maximum standardized uptake value (SUVmax) in 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) may be of prognostic significance for patients with malignant pleural mesothelioma (MPM). This retrospective study aimed to investigate the prognostic value of the SUVmax in patients with MPM. Materials and methodsMedical records were retrospectively reviewed for the patients who were diagnosed with histopathologically proven MPM between 2009 and 2018 at Samsung Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Among these, 18 F-FDG PET/CT, which reflects glucose utilization of target tissues, not only allows the optimal choice of therapeutic management but also assesses prognosis 12 16 . Previous studies with several kinds of malignancies have reported the clinical usefulness of using metabolic parameters of 18 F-FDG PET/CT, such as maximum standardized uptake value (SUVmax), metabolic tumour volume (MTV), and total lesion glycolysis (TLG), for prediction of prognosis 17 20 . However, there are only a few studies focusing on the prognostic value of metabolic parameters in patients with rectal cancer 21 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these, 18 F-FDG PET/CT, which reflects glucose utilization of target tissues, not only allows the optimal choice of therapeutic management but also assesses prognosis 12 16 . Previous studies with several kinds of malignancies have reported the clinical usefulness of using metabolic parameters of 18 F-FDG PET/CT, such as maximum standardized uptake value (SUVmax), metabolic tumour volume (MTV), and total lesion glycolysis (TLG), for prediction of prognosis 17 20 . However, there are only a few studies focusing on the prognostic value of metabolic parameters in patients with rectal cancer 21 25 .…”
Section: Introductionmentioning
confidence: 99%
“…3,[5][6][7] Unfortunately, imaging can under estimate the disease burden, 7 and aggressive types of disease exist within the more indolent epithelioid subtype, which limits the prognostic accuracy of these characteristics. 7,8 AbdelRahman applied the staging method used by the eighth American Joint Committee on Cancer (AJCC) to 5382 patients with malignant pleural mesothelioma and determined that prognostic per formance was poor, and that better staging systems are needed for patients with this disease. 9 Several studies have tried to further refine histological classification to better understand the heterogeneity of epithelioid disease, [10][11][12][13][14][15] including Courtiol and colleagues' study 16 in which they used a deep learningbased approachknown as MesoNet-to examine wholeslide digitised images to predict overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…According to 2018 American Society of Clinical Oncology (ASCO) guidelines, diagnosis of MPM is made using thoracentesis with cytology of fluid or thoracoscopic biopsy, while FDG PET/CT should be obtained as part of initial staging [6]. In addition to its value in staging MPM, SUVmax on FDG PET/CT has been shown to have prognostic value, predicting overall survival [7], especially in MPM of the epithelioid subtype [8].…”
Section: Discussionmentioning
confidence: 99%